Case report: Interstitial implantation radiotherapy combined with immunotherapy and GM-CSF in oligometastatic platinum-resistant ovarian cancer - Qin, Yi; Huang, Shangke; Tang, Junli; Fan, Yu; Deng, Xiangyu; Guan, Ping; Zhang, Zhenhua; Wen, Qinglian; Li, Dan (Frontiers in Immunology, 2024)
Background: Treatment for platinum-resistant ovarian cancer is challenging. Currently, platinumresistant ovarian cancer is typically treated with non-platinum single-agent chemotherapy ± bevacizumab, but the prognosis is often extremely poor. In the treatment of platinum-resistant ovarian cancer patients, reports of triple therapy with interstitial implantation radiotherapy combined with immunotherapy and granulocyte-macrophage colony-stimulating factor (GM-CSF) (PRaG for short) are relatively rare. Case description: Here, we report a patient with oligometastatic platinumresistant ovarian cancer. The patient achieved partial response (PR) of the lesion and sustained benefit for more than six months after receiving interstitial implantation radiotherapy combined with immunotherapy along with GM-CSF. Conclusions: This triple therapy may provide additional options for these patients.